Dosimetric Comparison of Craniospinal Irradiation Using Different Tomotherapy Techniques. (August 2015) - Zhang, X.; Penagaricano, J.; Han, E. Y.; Morrill, S.; Hardee, M.; Liang, X.; Gupta, S. K.; Corry, P. M.; Ratanatharathom, V.
The objective of this study is to compare the new and conventional tomotherapy treatment techniques and to evaluate dosimetric differences between them. A dosimetric analysis was performed by comparing planning target volume (PTV) median dose, 95% of PTV dose coverage, Paddick conformity index (CI), homogeneity index (HI), whole-body integral dose, and OAR median doses. The beam on time (BOT) and the effect of different jaw sizes and pitch values was studied. The study results indicated that the PTV dose coverage for all the techniques was comparable. Treatment plans using dynamic jaw reduced OAR doses to structures located at the treatment field edge compared to fixed jaw plans. The HT-3DCRT plans resulted in higher OAR doses to kidney, liver, and lung compared to the other techniques, and TD-IMRT provided the best dose sparing to liver compared to other techniques. Whole-body integral dose differences were found to be insignificant among the techniques. BOT was found to be higher for fixed jaw treatment plan compared to dynamic jaw plan and comparable between all treatment techniques with 5-cm dynamic jaw. In studying effect of jaw size, better OAR sparing and HI were found for 2.5-cm jaw but at the expense of doubling of BOT as compared to 5-cm jaw. There was no significant improvement found in OAR sparing when the pitch value was increased. Increasing the pitch from 0.2 to 0.43, the CI was improved, HI improved only for 5-cm jaw size, and BOT decreased to approximately half of its original time.